An alternative approach to the synthesis of peptides containing a cystathionine bridge. Issue 23 (9th June 2016) - Harjani, Jitendra R.; Yap, Beow Keat; Norton, Raymond S.; Baell, Jonathan B.
Abstract: A new method for the synthesis of cystathionine containing cyclic peptides has been developed. Conventionally such systems are typically made with relatively late-stage on-resin cyclisation involving reaction between a chlorohomoalanine and cysteine residue. We offer a different approach involving early incorporation of a cystathionine residue through on-resin reaction between a cysteine residue and an N -Alloc iodohomoalanine cumyl ester. Subsequent cyclisation then involves amide bond formation. The success of this method was demonstrated by applying it to the synthesis of a cystathionine analogue of the disulfide bridge cyclic peptide, N -acetylated cyclic peptide c[CVDINNNC]-NH2, a biologically active iNOS binding epitope mimetic that binds tightly to the protein, SPSB2. Our method expands the repertoire of synthetic options towards the construction of cystathionine containing cyclic peptides. Graphical abstract: